The Effectiveness of Life Skills Training on Self-Handicapping among Students - Taghipour, Zahra; Naseri, Ali (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2026)
Objective: This study aimed to examine the effectiveness of life skills training in reducing self-handicapping behaviors and their components among master’s students.Methods and Materials: This applied, quantitative study used a semi-experimental pretest–posttest design with a control group and a two-month follow-up. The statistical population comprised all master’s students in Economic Management at the Islamic Azad University, Shiraz Branch, during the 2024–2025 academic year. Using convenience sampling, 78 students were selected and randomly assigned to an experimental group (n = 39) and a control group (n = 39). The experimental group participated in ten 45-minute sessions of life skills training based on Klinke’s (1994) protocol, covering self-awareness, empathy, communication, anger management, problem-solving, stress management, decision-making, creative and critical thinking, and emotional regulation. Data were collected using the Self-Handicapping Questionnaire developed by Jones and Rhodewalt (1978) and analyzed through analysis of covariance (ANCOVA) and multivariate analysis of covariance (MANCOVA) using SPSS 26.Findings: The results revealed significant reductions in total self-handicapping and its components among the experimental group compared to the control group at the posttest stage (p < .001). ANCOVA results indicated strong intervention effects on total self-handicapping (F = 92.34, η² = .591), effort (F = 32.25, η² = .342), and negative mood (F = 21.65, η² = .259), with a moderate effect on excuse-making (F = 8.90, p = .004, η² = .126). The follow-up analysis confirmed the persistence of effects after two months, except for the excuse-making component (p > .05).Conclusion: Life skills training effectively reduces self-handicapping and its cognitive-emotional components among university students and maintains its impact over time, highlighting its importance as a preventive and developmental intervention in higher education.